Buddhist culture as a safeguard for the subjective happiness of Chinese residents: mitigating anxiety regarding housing prices, unemployment, and inequality - Tan, Shuying; Fang, Peijie; Shi, Wenxiang; Du, Shukai (Frontiers in Psychology, 2023)
This study examines whether Buddhist culture in China can safeguard the subjective happiness of residents by mitigating the detrimental impact of adversity. Considering Chinese traditional culture and referencing Baidu Search Index data, we focus on three sources of anxiety that are currently troubling Chinese residents: housing prices, unemployment, and inequality. We employ the frequency of droughts and floods that occurred during the Ming and Qing dynasties as instrumental variables for the local density of Buddhist culture to avoid endogeneity problems. Empirical analysis based on microdata shows that Chinese Buddhist culture demonstrates the ability to alleviate the negative effects of housing price pressures, unemployment anxiety, and perceived inequality on subjective well-being. Mechanism analyses reveal that Chinese Buddhist culture plays a role in ameliorating the adverse impacts of housing and unemployment pressures on factors such as job satisfaction, physical health status, social trust, and expectations of future social standing. Moreover, it works to reduce inclinations toward social comparisons, thereby acting as a safeguard for happiness. Heterogeneity analysis shows that this insurance effect is more pronounced among vulnerable groups, including those in rural areas, middle-aged and elderly demographics, individuals with fewer social connections, lower social security coverage, and suboptimal health conditions. This study expands the landscape of happiness economics research and provides novel evidence about the correlation between religion and happiness.